Utilization of Intraoperative TEE to Assess Supraventricular Tachycardia-Inducing Right-Sided Cardiac Compression by the Liver, Post-Liver-Transplantation Status. (12th March 2015) - Stoll, W. David; Hand, William R.; Rohan, Vinayak S.; Gaddy, Parker M.; Reeves, Scott T.; Chavin, Kenneth D.
Abstract : This unique and interesting case report involves a patient who recently underwent a combined liver and kidney transplant (due to autosomal dominant polycystic kidney disease) and subsequently suffered from episodes of supraventricular tachycardia (SVT) secondary to the new liver graft compressing the right atrium and ventricle. After this was diagnosed, the patient underwent operative plication of the right hemidiaphragm. Intraoperative transesophageal echocardiography was used to demonstrate cardiac compression from the liver and demonstrate resolution of compression after plication of the hemidiaphragm.